Understanding the effects of training on underwater undulatory swimming performance and kinematics - Ruiz-Navarro, J. J.; Cano-Adamuz, M.; Andersen, J. T.; Cuenca-Fernández, F.; López-Contreras, G.; Vanrenterghem, J.; Arellano, R. (Sports Biomechanics, 2021)
In swimming, the underwater phase after the start and turn comprises gliding and dolphin kicking, with the latter also known as underwater undulatory swimming (UUS). Swimming performance is highly dependent on the underwater phase; therefore, understanding the training effects in UUS and underwater gliding can be critical for swimmers and coaches. Further, the development of technique in young swimmers can lead to exponential benefits in an athlete's career. This study aimed to evaluate the effects of a training protocol on UUS and underwater gliding performance and kinematics in young swimmers. Seventeen age group swimmers (boys=10, girls=7) performed maximal UUS and underwater gliding efforts before and after a seven-week training protocol. Time to reach 10 m; intra-cyclic mean, peak, and minimum velocities; and gliding performance improved significantly after the training protocol. The UUS performance improvement was mostly produced by an improvement of the upbeat execution, together with a likely reduction of swimmers' hydrodynamic drag. Despite the changes in UUS and gliding, performance was also likely influenced by growth. The findings from this study highlight kinematic variables that can be used to understand and quantify changes in UUS and gliding performance.